i-Sirah Board Game: stories from the Quran as a pathway to Islamic civilisation - Ismail, Nur Farrah Syazwanie; Saidin, Nurhafizah; Aling, Noor Asiah; Johari, Shapizan; Zulkifli, Muhammad Firdaus (Centre of Foundation Studies Universiti Teknologi MARA Cawangan Selangor, Kampus Dengkil, 2025)
i-Sirah Board Game is an educational innovation designed to promote students’ understanding of Islamic civilisation through Quranic narratives and reflective learning. It is developed for pre-university students at the Centre for Foundation Studies, International Islamic University Malaysia (CFS IIUM). This digital board game integrates elements of i-Sirah Interactive and Qur'anic tadabbur. The game board is divided into four sections, each representing different juzuk of the Quran. As students move their pieces by rolling the dice, they land on destinations linked to specific Quranic verses. At each point, they watch a short video about Prophet’s Sirah story and then answer related questions. This process helps students connect Quranic guidance with historical lessons and moral values. The originality of the innovation lies in its combination of narrative storytelling, gamification, and Quran-based learning, making Sirah both engaging and interactive. It fosters active learning, critical thinking, and collaboration among students, while deepening their appreciation for Islamic history and civilisation. Initial trials indicate strong positive responses, including increased engagement to learn Sirah, better attention to historical lessons, and improved satisfaction on meaningful learning on Sirah. The game is adaptable for different age levels and learning outcomes, making it applicable in schools, madrasahs, and learning centres. The digital format ensures broad accessibility, and with further development, the game holds strong potential for educational commercialisation in both local and international Islamic education settings.